2024
DOI: 10.9734/jocamr/2024/v25i2518
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Effect of Urtica dioica on Locomotor Behaviour of Mice Using the Open Field Maze Task

DI Izunwanne,
SK Mobisson,
CC Nwafor
et al.

Abstract: Introduction: It is generally believed that the presence of some neuroactive phytochemicals such as acetylcholine, histamine, serotonin, tannins etc. in Urtica dioica may yet possess the key to the management of certain neurological and behavioral conditions at an easily accessible and affordable rates. The growing acceptance of alternative medicine in Nigeria and the world at large has necessitated this research work so as to ensure that the general/consuming public is properly guided. Objective: This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
0
1
Order By: Relevance
“…Indeed, the 96 hpf larval motion trail record indicated that CPF exposure resulted in notable behavioral changes in terms of the emotional trail and swimming distance. The decreased motility of UDE larvae compared to the Ctrl group was contradictory with the finding of DI Izunwanne et al, who reported in a recent study that a repeated administration of Urtica dioica enhanced locomotory behavior in mice [86].…”
Section: Discussioncontrasting
confidence: 75%
“…Indeed, the 96 hpf larval motion trail record indicated that CPF exposure resulted in notable behavioral changes in terms of the emotional trail and swimming distance. The decreased motility of UDE larvae compared to the Ctrl group was contradictory with the finding of DI Izunwanne et al, who reported in a recent study that a repeated administration of Urtica dioica enhanced locomotory behavior in mice [86].…”
Section: Discussioncontrasting
confidence: 75%